Prevalencia de pacientes con Diabetes Mellitus tipo 2 en tratamiento y la presencia de patologías tiroideas en el hospital SOLCA Loja 20102015 - Arias Román, Ana Belén (2018)
Abstract: With the purpose of establishing the prevalence of the patients with diabetes type 2 treated with oral hypoglycemic agents, insulin or its combinations and the development of thyroid pathologies in the Hospital of SOLCA Loja in the period of 2010-2015 we came up with the following study, which is quantitative, descriptive and transversal. The universe was all the patients diagnosed with type 2 diabetes and applying the exclusion criteria we worked with a total of 89 patients. Results: the 21% (n=19) developed thyroid pathologies being hypothyroidism the most common in the 14% (n=12), followed by thyroiditis in the 3% (n=3). Hypothyroidism was present in 15% (n=3) of the patients who received metformin, the 7.2% (n=2) of the ones that were treated with metformin+glibenclamide, the 3.6% (n=1) of the patients treated with metfromin+glimepiride and the 2.4% (n=1) of the individuals receiving insulin+metformin+glibenclamide. We concluded that hypothyroidism was the thyroid pathology most patients developed related with the use of metformin as monodosis or in combinations.